The prevalence of allergy diseases and markers of sensitization in schoolchildren of the city Tomsk and Tomsk Region according to data of the International Study of asthma and Allergy in Childhood (ISAAC) - Ye. M. Kamaltynova (Бюллетень сибирской медицины)
The article includes information about the prevalence of asthma, allergic rhinitis and eczema among childhood in the program of the International Study of asthma and Allergy in Childhood — ISAAC. The present results of skin prick-test to describe sensitization in boys and girls 7—8 and 13—14 year old, living in different environments. The results indicate a lower prevalence of skin allergy in rural areas.